Estudio de factibilidad para la creación de una aplicación de eventos sociales (2020)
Colombia has a diversity of regional cultures that enrich and provide the country with a different characterization from other Latin American countries; The joy and fun that distinguishes Colombians anywhere in the world prevails in all of them, parties, dances and social gatherings are insignia that have endured in the history of the country.